(untitled) (Physical Education, Health and Social Sciences, 2025)
Abris precatorius is of great significance in medicine as it is a great source of variety of therapeutic compounds including abrin protein. Abrin exhibits anticancer and antimicrobial potential. However, its use is limited due to its toxicity. This toxicity might be reduced through genetic alterations of protein. Current study was initiated to unravel its physicochemical and structural features that might be useful for its manipulations and optimum exploitation in medicine. For this purpose, initially the amino acid sequence was obtained from NCBI (National Center for Biotechnology Information) database and subjected to characterization via SOPMA, PROTPARAM, SWISS-MODEL and TMHMM server and CB-Dock-2 docking platform. The values of alpha helix, extended strand and random coil in abrin protein were analyzed as 12.57, 29.84 and 57.59%, respectively. Protein was identified with 382 amino acids, 5.58 pI, 32.76 instability index, 79.61 aliphatic index and -0.376 GRAVY. Protein exhibited transmembrane helix and highly complex 3D configuration. Docking analysis revealed its C4 pocket as the primary binding site. The characteristics explored in current study might help in optimizing the medicinal applications of abrin protein via providing information for structural alterations.